Climate Change Risks in Financial Business - Krasnova Iryna V.; Prymostka Liudmyla O.; Lavreniuk Vladyslav V. (Problemi Ekonomiki, 2021)
The article is aimed at identifying, firstly, the features and the ways in which climate change influences the profile of financial business, and secondly, financial risks modification while taking into account climate change risks. Climate change is global, it causes new challenges for corporations, financial institutions and central banks, and for economy, as a whole. Statistics on the scale of the threatening impact produced by climate-re;ated risks on economy and its financial sector are presented. It is noted that the aggregate impact of climate change risks significantly exceeds the losses from the financial markets collapse. In particular, due to the natural disasters in 2020, the world economy suffered losses of about US$ 200 billion. The properties of climate-related risks are systematized and generalized, including the following: unpredictability, radical uncertainty, complex dynamics, chain effect, irreversibility, nonlinearity. Due to the high level of uncertainty, the problem of integrating climate change risks into the risk management system of financial institutions remains particularly complex. The ways in which risks generated by global climate change transform into financial risks are determined. It is noted that, despite the threatening impact of damage caused by extreme weather events and climate catastrophes, the management of these risks is still characterized by a low level of penetration into the system of risk-oriented management of financial institutions. In order for the financial business to effectively manage risks taking into account climate change, innovative approaches of strategic importance have been suggested, namely, green bonds and disaster bonds. The financial stability and sustainable dynamic development of economy will depend on the performance of financial institutions in implementing their policies in this area.